Biocatalytic synthesis, antimicrobial properties and toxicity studies of arginine derivative surfactants - Fait, María Elisa (2015)
Abstract Two novel arginine-based cationic surfactants were synthesized using as biocatalyst papain, an endopeptidase from Carica papaya latex, adsorbed onto polyamide. The classical substrate N α-benzoyl-arginine ethyl ester hydrochloride for the determination of cysteine and serine proteases activity was used as the arginine donor, whereas decyl- and dodecylamine were used as nucleophiles for the condensation reaction. Yields higher than 90 and 80 % were achieved for the synthesis of N α-benzoyl-arginine decyl amide (Bz-Arg-NHC10) and N α-benzoyl-arginine dodecyl amide (Bz-Arg-NHC12), respectively. The purification process was developed in order to make it more sustainable, by using water and ethanol as the main separation solvents in a single cationic exchange chromatographic separation step. Bz-Arg-NHC10 and Bz-Arg-NHC12 proved antimicrobial activity against both Gram-positive and Gram-negative bacteria, revealing their potential use as effective disinfectants as they reduced 99 % the initial bacterial population after only 1 h of contact. The cytotoxic effect towards different cell types of both arginine derivatives was also measured. Bz-Arg-NHCn demonstrated lower haemolytic activity and were less eye-irritating than the commercial cationic surfactant cetrimide. A similar trend could also be observed when cytotoxicity was tested on hepatocytes and fibroblast cell lines: both arginine derivatives were less toxic than cetrimide. All these properties would make the two novel arginine compounds a promising alternative to commercial cationic surfactants, especially for their use as additives in topical formulations.